(3x-1)(10x-3)=0

Simple and best practice solution for (3x-1)(10x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-1)(10x-3)=0 equation:


Simplifying
(3x + -1)(10x + -3) = 0

Reorder the terms:
(-1 + 3x)(10x + -3) = 0

Reorder the terms:
(-1 + 3x)(-3 + 10x) = 0

Multiply (-1 + 3x) * (-3 + 10x)
(-1(-3 + 10x) + 3x * (-3 + 10x)) = 0
((-3 * -1 + 10x * -1) + 3x * (-3 + 10x)) = 0
((3 + -10x) + 3x * (-3 + 10x)) = 0
(3 + -10x + (-3 * 3x + 10x * 3x)) = 0
(3 + -10x + (-9x + 30x2)) = 0

Combine like terms: -10x + -9x = -19x
(3 + -19x + 30x2) = 0

Solving
3 + -19x + 30x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(3 + -10x)(1 + -3x) = 0

Subproblem 1

Set the factor '(3 + -10x)' equal to zero and attempt to solve: Simplifying 3 + -10x = 0 Solving 3 + -10x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -10x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -10x = 0 + -3 -10x = 0 + -3 Combine like terms: 0 + -3 = -3 -10x = -3 Divide each side by '-10'. x = 0.3 Simplifying x = 0.3

Subproblem 2

Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333

Solution

x = {0.3, 0.3333333333}

See similar equations:

| 3x+3(6x-12)=132 | | 3r-4rs+2s= | | 0.07=56 | | 72=9g | | 2X-21+3X-34=180 | | -4(5x+2)+3(x-3)= | | 2w-3(3w+5)=3w+5 | | -8x-5y=15 | | 35-19=3(x-3) | | ?(2x-4)+5=-?(x+1) | | 3x^3+13x^2-16=0 | | 48x^2-16x-20=0 | | -138-6(6b-7)= | | 2n-1=-11 | | 4x+8y=52 | | 3n-8=-20 | | 4x-10=12+4(x+8) | | 2-c=29 | | ?(2x-4)=-?(x+1) | | 4t-1=5(t+5) | | 3x=7x+20 | | 5(6+3r)+7127= | | 13mn-5nm+2mn= | | 6+5ln(2x-1)=21 | | 2x+14=8-3y | | x^2-15x+(56.25)=8 | | 1.6=2y+7.8 | | 4-n=6 | | 5=25/d | | 8x-15x-6=40 | | 7.5r+2=-284 | | 7(5x-10)=4(4x-8) |

Equations solver categories